Exposure of Workers of Ectatomma brunneum Smith (Hymenoptera: Formicidae: Ectatomminae) to ant Baits Containing Different Active Ingredients under Laboratory Conditions - Tofolo, Viviane Cristina; Giannotti, Edilberto; Pizano, Marcos Aparecido (EntomoBrasilis, 2015)
This work evaluated the short-range mortality of workers of Ectatomma brunneum Smith when exposed to ant baits in laboratory, in order to verify if the attractiveness of this non-target species by ant baits intended to be used in the control of leaf-cutting (target) ants might be harmful to the population studied. Workers were exposed in laboratory for 48 hours to ant baits used in pastures to control the leaf-cutting ants Atta capiguara Gonçalves (Formicidae: Attini) and Atta bisphaerica Forel (Formicidae: Attini), the major species that cause damage to pastures. The following formulations of granular bait ant-killer active ingredients sulfluramid 0.3%, fipronil 0.003% and chlorpyrifos 0.45% were used. The experiment outline was composed by groups of 30 workers exposed to 10g of moistened ant baits, using three repetitions. Daily follow-up on mortality was performed for 20 days, recording dead and intoxicated workers. The control group received only 10g of moistened citric pulp. From the results achieved, survival curves as a function of observation time were plotted using the Kaplan-Meier method and compared applying the Logrank test (nonparametric) at 5% significance level. The results revealed that the three active ingredients tested were toxic and the population reduced 35.56% in the treatment with chlorpyrifos, 31.11% with sulfluramid and 30% with fipronil. Exposição de Operárias de Ectatomma brunneum Smith (Hymenoptera: Formicidae: Ectatomminae) a Iscas Formicidas Contendo Diferentes Ingredientes Ativos em Condições de Laboratório Resumo. Este trabalho avaliou a mortalidade a curto prazo de operárias de Ectatomma brunneum Smith expostas a iscas formicidas em laboratório, a fim de verificar se a capacidade de atração desta espécie não-alvo a formicidas destinadas ao controle de formigas cortadeiras (alvo) pode ser prejudicial para a população estudada. As operárias foram expostas em laboratório por 48 horas a iscas formicidas utilizadas em pastagens para controlar as formigas cortadeiras Atta capiguara Gonçalves (Formicidae: Attini) e Atta bisphaerica Forel (Formicidae: Attini), as principais espécies que causam danos às pastagens. Foram utilizados os seguintes ingredientes ativos: sulfluramida 0,3%, fipronil 0,003% e clorpirifos 0,45%. O experimento foi composto por grupos de 30 operárias expostas a 10g de formicidas, usando três repetições. Foi realizado o acompanhamento diário da mortalidade durante 20 dias, registrando-se o número de operárias mortas e intoxicadas. O grupo controle recebeu apenas 10g de polpa cítrica umedecida. A partir de resultados obtidos, as curvas de sobrevivência em função do tempo de observação foram plotadas usando o método de Kaplan-Meier, e comparadas com aplicação do Logrank test (teste não-paramétrico) em nível de significância de 5%. Os resultados revelaram que os três ingredientes ativos testados foram tóxicos e a população reduzida em 35.56% no tratamento com clorpirifós, 31,11% com sulfluramida e 30% com fipronil.